Fever of unknown origin diagnostic protocol for developing countries - ROMO, JESÚS (2004)
Vital signs like the fever usually are frustrating for the binomial doctor-patient; as such it is indispensable to have in mind a series of steps that direct us to the etiologic diagnosis of this pathological modality. We cannot face this disturbance by following protocols recommended by authors of the first world, as many times we remain halfway, constituting a loss of time and frustration. That is why we need to reorganize an established affluent protocol. In this paper, the English diagnosis protocol is reorganized in order to deduce the etiologic factor in Fever of unknown origin (FOD). Most of the authors expert on the subject recommend four divided diagnosis phases according to the tools (technological and scientific) of diagnosis. The intention of this paper is to regroup the diagnosis modality in benefit of hospital units of Latin America and other developing countries. We present a format easy to follow and that without doubt will give good results for the etiology tracking of this problem.